Misty of Chincoteague - Henry, Marguerite; Dennis, Wesley (New York : Scholastic, 1947)
Two youngster's determination to own a Chincoteague pony is greatly increased when the phantom and her colt are among those rounded up for the yearly auction.
Keywords: Pony -- Fiction